Autobondade e adoecimento em cuidadores de idosos com transtorno neurocognitivo: o efeito mediador da sobrecarga - Alves, Silvia Sanaly de Lucena (2022)
Major Neurocognitive Disorder results in a decrease in intellectual faculties, changes in personality and behavior, having a degree of impact sufficient to cause loss of autonomy and quality of life. With this loss, these people start to rely on the care of family members or friends who assume the implicit commitment to assist, on a continuous basis and without remuneration, the needs of the caregiver. The dynamics involved in this care process can generate stressful conditions capable of compromising the caregiver's health and well-being. However, the act of caring can be seen as less threatening or evaluated by the caregiver as a situation that he is able to face, with internal and external resources. In this perspective, the concept of self-kindness was associated with positive outcomes that appear to be beneficial for caregivers. Therefore, the present study aims to analyze the mediating role of care overload in the relationship between self-kindness and physical and mental illness in informal caregivers of people with NMD. For this, 149 informal caregivers participated in this study. All volunteers answered the questionnaires that were made available online. The results indicated that there is a statistically significant indirect effect (indirect effect = -.316, BSE = .126, CI 95% BCa [-.59; -.10]) of self-kindness on the caregiver's physical illness, through overload. On the other hand, this effect was partial considering the relationship between self kindness and the caregiver's mental illness, through overload, when the mediator entered the prediction model, the indirect effect was significant (indirect effect = -.092, BSE = .034, IC 95% BCa [-.16; -.03). However, the direct effect of self-kindness on mental illness was also significant (c' = -.233; BSE = -.062, 95% CI BCa [-.35, -.11]. The results demonstrate that self-kindness can favor a better perception of care burden.